Networks and Network Analysis for Defence and Security - Masys, Anthony J. (Lecture Notes in Social Networks, 2014)
Networks and Network Analysis for Defence and Security discusses relevant theoretical frameworks and applications of network analysis in support of the defence and security domains. This book details real world applications of network analysis to support defence and security. Shocks to regional, national and global systems stemming from natural hazards, acts of armed violence, terrorism and serious and organized crime have significant defence and security implications. Today, nations face an uncertain and complex security landscape in which threats impact/target the physical, social, economic and cyber domains. Threats to national security, such as that against critical infrastructures not only stem from man-made acts but also from natural hazards. Katrina (2005), Fukushima (2011) and Hurricane Sandy (2012) are examples highlighting the vulnerability of critical infrastructures to natural hazards and the crippling effect they have on the social and economic well-being of a community and a nation. With this dynamic and complex threat landscape, network analysis has emerged as a key enabler in supporting defence and security. With the advent of 'big data' and increasing processing power, network analysis can reveal insights with regards to structural and dynamic properties thereby facilitating greater understanding of complex networks, their entities, interdependencies, vulnerabilities to produce insights for creative solutions. This book will be well positioned to inform defence, security and intelligence professionals and researchers with regards to leading methodologies and approaches.